Gender Empowerment in Agriculture Interventions: What Are We Still Missing? Evidence From a Randomized-Controlled Trial Among Coffee Producers in Honduras - Rubio-Jovel, Karla (Frontiers in Sustainable Food Systems, 2021)
Latin-American coffee production has largely relegated women to specific family labor tasks, such as berry picking or cooking. But recent years have seen an increasing number of interventions to empower women in the agricultural sector, including coffee. As a contribution to the growing literature on women's empowerment in agriculture, this article draws on a randomized-controlled trial (RCT) to evaluate a gender empowerment project among coffee producers in Honduras. Previous RCT evaluations of gender empowerment interventions have focused on average treatment effects and paid less attention to the diversity of responses in the sample. This article evaluates the effect of a project to empower women in Honduras' coffee sector but pays attention to how the intervention interacted with the amount of land owned by women to produce different outcomes. The intervention consisted of 12 workshops offered to families in 10 coffee-producing groups. The baseline and end-line surveys (2016–2018) included a sample of 88 families (41 intervention and 47 control, from 4 to 5 communities respectively). Results showed limited effects of the intervention on women's empowerment for the pooled sample, but it found heterogeneous positive effects for land-owning women. Women who owned land and received the treatment scored fewer points on a deprivation score, had input over more decisions related to the use of household income, and were more satisfied with their leisure time. For quantity of land owned, this article also found positive heterogeneous effects for the same variables, and additionally for confidence speaking in public. Results suggest that projects to empower women might benefit from a more nuanced approach to the heterogeneity within the target population.